Pengaruh Perendaman Minuman Isotonik Terhadap Kekerasan Permukaan Email Gigi - Sari Dewiyani; Ratih Widyastuti; Fauzi Saeful Rohman (FKG Universitas Syiah Kuala, 2024)
Demineralization is the process of losing minerals in tooth enamel when the enamel is in a pH environment below 5.5. Email is the outer layer of the crown anatomy, including the hardest part of the body could dissolved when consume isotonic drinks are consist of various types of acids which reduce the pH of the oral cavity. At a low pH oral cavity, tooth demineralization can occur.. Hardness of tooth enamel is a physical trait that is owned by the tooth part which is an email that can be measured using Micro Vickers Hardness with VHN units. Objective: To explain the effect of soaking isotonic drinks on hardness of tooth enamel. Methods: Six samples of premolar teeth post orthodontic treatment extraction were then immersed in isotonic drinks for 5 minutes/day for 7 days. After that, the hardness measurement was done using Micro Vickers Hardness. Results: independent T-test test obtained p = 0.03 (p 0.03) there were differences in the level of tooth enamel surface hardness between the treatment group and the control group. Conclusion: Isotonic drinks can reduce the hardness of tooth enamel surfaces.